Mixed FTS/H∞ control of vehicle active suspensions with shock road disturbance. Issue 6 (3rd June 2019) - Xue, Wenping; Li, Kangji; Chen, Qian; Liu, Guohai
ABSTRACT: In consideration of the feature of shock road disturbance, the mixed finite-time stability (FTS)/H ∞ control problem for vehicle active suspensions is addressed in this paper. First, the definition of input–output finite-time stability (IO-FTS) with anH ∞ bound is provided, and a sufficient condition guaranteeing the mixed IO-FTS/H ∞ performance for a linear system is proposed. Second, the control issue for a 2-DOF (degree of freedom) quarter-car active suspension with shock road disturbance is suitably formulated as a mixed FTS/H ∞ control problem. Then, sufficient criteria for the design of a state-feedback controller are presented, which can be reduced to the solvability of a linear minimisation problem with some fixed parameters. Finally, simulation results are given to show the applicability and effectiveness of the developed control methodology.